Development of an Efficient Micropropagation System for Four Commercially Important Banana Genotypes of Bangladesh (Journal of Bio-Science, 2026)
Under this study, four important commercial banana genotypes, such as Grand Naine (G-9), Sabri, Mehersagor and Jahaji, were considered, and experiments were carried out to investigate the effects of different cytokinins (BAP, KIN) and auxins (IAA, IBA, NAA) on shoot initiation and multiplication. Excised shoot-tips were used as explants and cultured on MS medium supplemented with various concentrations and combinations of BAP, IAA, and NAA to evaluate regeneration efficiency. The highest response of explants (78%) and maximum number of shoots per explant (5.04) were observed with 3.5 mg/L BAP + 1.5 mg/L IAA in G-9. In Sabri, the highest response of explants (65%) and maximum number of shoots per explant (5.50) were observed with 2.5 mg/L BAP + 1.0 mg/L Kin. The variety Mehersagor showed the highest response in on callus induction and regeneration (67%) and maximum number of shoots per explant (6.22), where 4.5 mg/L BAP + 2.0 mg/L IAA were used. The Jahaji showed the maximum number (72%) of shoots per explant (6.24). G-9 showed the highest number of roots (5.75) with 2.0 mg/L of IAA in MS medium. In Sabri, 5.81 roots were observed with 1.50 mg/L of IBA. In Mehersagor, the maximum number of roots (6.66) was recorded at 1.50 mg/L of IBA. Similarly, in Jahaji, 6.69 roots were observed with 1.00 mg/L of IBA. The regenerated healthy rooted plantlets were transferred from the culture bottle to soil in small plastic pots and were kept at outdoor environment, the survival rate was 88.89%. After proper acclimatization, the well-rooted plants were successfully transferred and hardened. This technology presents significant prospects for advancing commercial banana production, particularly by providing researchers with a reliable platform for large-scale propagation and genetic improvement.J. Bio-Sci. 33(1): 93-100, 2025